Superior responsibility under the Rome statute and its applicability to constitutional monarchy: an appraisal - Hamid, Abdul Ghafur@Khin Maung Sein; Mohd Kamal, Mohd Hisham; Lallmahamood, Muhannad Munir; Torla, Areej (IIUM Press, 2021)
The doctrine of superior responsibility has been embedded in Article 28 of the Rome Statute of the International Criminal Court, which enunciates the responsibility of both military commanders and civilian superiors. In the context of constitutional monarchy, the monarchs, although they are civilians, are entrusted with the position of commanders-in-chief. In some constitutional monarchies like Malaysia, there were States that opposed accession to the Rome Statute on the simple ground that their respective monarchs could be indicted and punished under the Rome Statute. The main objective of this paper, therefore, is to examine whether constitutional monarchs could be responsible under this doctrine. The paper focuses on the analysis of the elements of superior responsibility by referring to the authoritative commentaries of Article 28 and constitutional practices of three selected constitutional monarchies: the United Kingdom, Japan, and Malaysia. It concludes with the finding that constitutional monarchs could not be held responsible because they have to act on the advice of the government and do not possess the effective and operational control over their subordinates as required under the Rome Statute.